Estrategias de marketing y su impacto en las organizaciones - Puello Cabarcas, Deiber (Corporación Universitaria Americana, 2020)
Nowadays, organizations face an increasingly changing and competitive market, and to remain in it they must not only design and implement strategies to achieve greater efficiency in their production process, but they must also produce and offer goods or services that satisfy the tastes, desires and needs of present and future consumers, where a very close relationship must be established with them to get to know their requirements. Marketing is one of the business functions that must keep up with these requirements. Marketing as a process has the tools to identify and communicate the benefits offered by a business to its target market, and focuses on creating strategies to achieve it.